Assessment of the socio-economic indicators of the railway transport enterprise in the context of the strategic development of the country's economy and analysis of its results - Bobojonova Zarnigor (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
In the context of the strategic development of the country's economy, the transport system, especially the railway transport network, is of particular importance. As an important infrastructural link of the national economy, this sector is important in ensuring the continuity of production processes, supporting export-import operations, strengthening interregional economic ties, and developing domestic market integration.